PENGARUH KUALITAS LAYANAN DAN LOKASI TERHADAP KEPUASAN PENGUNJUNG MUSEUM FATAHILLAH JAKARTA - Rieke Rahardjo; Sinton Siahaan; Nova Eviana (Eduturisma, 2017)
The purpose of this research is to analyze effect of quality of service and location toward the visitors’ satisfaction of the Museum Fatahillah, both partially and simultaneously. The data were collected by distributing questionnaires to 100 Fatahillah Museum, using accidental sampling technique. The analysis used for this research is multiple linear regression. The result of the research shows that those variables partially and simultaneously affect toward satisfaction of museum visitors and also contribute 61.20% for it. Among variables, tourist attraction also becomes the most dominant variable to affect tourists satisfaction.